Case report of a huge serous ovarian cystadenoma in post hysterectomy woman - Trishala Anil Patil; Hemant Limaye; Ajit Mehta (Barpeta Obstetrics and Gynaecological Society, 2018)
A case of large benign serous cystadenoma in 68 year post hysterectomy woman presented with distension and pain in abdomen. Ultrasonography was suggestive of large multinucleated multiseptic cystic lesion extending from right adnexa up to right hypochondriac and epigastric region measuring 28 cm ×20 cm may be a complex ovarian cyst. Computed tomography (CT) showed 25.9 cm×15cm×23cm multiloculated cyst with multiple internal septations suggestive of ovarian neoplasm such as serious cystadenoma. Exploratory laparotomy with right ovarian cystectomy was done. Mass of 32 cm×25cm×15 cm size of weight 6.2kg was removed and send for frozen section which suggestive of benign serous cystadenoma.